DEMAND ANALYSIS OF SUBSIDIZED MORTAGAGE LOANS IN EAST JAVA - Natasha Claudia Ambarita; Sishadiyati (RADJA PUBLIKA, 2024)
To serve the housing needs of low-income people, the government provides a Subsidized Mortgage Loans program. Demand for subsidized mortgage loans in East Java is relatively low, while the population is growing every year. This is inseparable from the influence of several external factors. The purpose of the study is to analyze how the influence of Non Performing Loan (NPL), Inflation and Per Capita Income on Demand for subsidized mortgage in East Java. This research uses a quantitative approach in the form of time series from 2010-2023. In this study, multiple linear regression was used to test the effect of independent variables (NPL, Inflation and Per Capita Income) on the dependent variable (demand for subsidized mortgage loans in East Java). So the research results obtained that simultaneously the independent variables (NPL, Inflation and Per Capita Income) affect the dependent variable (demand for subsidized mortgage loans in East Java). Partially, only the NPL and per capita income variables have a positive and significant effect on the demand for subsidized mortgage loans in East Java, while the inflation variable has no significant effect on the demand for subsidized mortgage loans in East Java.